For the Anniversary of Dmitry Alekseevich Stashenkov - Kochkina Anna F.; Vyazov Leonid A. (Поволжская археология, 2019)
The article is dedicated to the anniversary of the famous Russian archaeologist D.A. Stashenkov. He brought his childhood dream of becoming an archaeologist into reality. Against the background of the main milestones of the jubilee biography, the main directions of his research in the field of archaeology of the Middle Volga region, related to the study of sites of Kiev type, Imenkovo culture, sites of Novinkovo type are characterized. At the same time, his works in the study of the Stone Age and the Eneolithic, Golden Horde antiquities and the history of archaeology are known and recognized.